There is a risk of kidney damage, while saving the heart (case report) - V. A. Batalin; O. M. Polyakova; M. V. Batalina (Столичная издательская компания, 2015)
The case study of contrast-induced acute kidney damage in patient with acute coronary syndrome and complex comorbidity with poor prognosis is presented.